Tlingit totem pole known as "Kyan" at Ketchikan, Alaska, ca. 1900. - Barley, H. C.
Caption on image: "Totem pole at Ketchikan" According to Viola Garfield: "The totem pole was referred to as the "Kyan totem pole". Surmounted by the crane, below is the Kyak a fabled bird of the mountains, and still below is the grizzly bear. Since the crane belongs to a different clan from the Kyak and Bear, this pole has on it the totems for man and his wife as was common among the Tlingit." PH Coll 246.171 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number